Scorpionfish BPI is highly active against multiple drug-resistant Pseudomonas aeruginosa isolates from people with cystic fibrosis - Holzinger, Jonas; Toelge, Martina; Werner, Maren; Ederer, Katharina Ursula; Siegmund, Heiko Ingo; Peterhoff, David; Blaas, Stefan Helmut; Gisch, Nicolas; Brochhausen, Christoph; Gessner, André; Bülow, Sigrid (eLife, 2023)
Chronic pulmonary infection is a hallmark of cystic fibrosis (CF) and requires continuous antibiotic treatment. In this context, Pseudomonas aeruginosa (Pa) is of special concern since colonizing strains frequently acquire multiple drug resistance (MDR). Bactericidal/permeability-increasing protein (BPI) is a neutrophil-derived, endogenous protein with high bactericidal potency against Gram-negative bacteria. However, a significant range of people with CF (PwCF) produce anti-neutrophil cytoplasmic antibodies against BPI (BPI-ANCA), thereby neutralizing its bactericidal function. In accordance with literature, we describe that 51.0% of a total of 39 PwCF expressed BPI-ANCA. Importantly, an orthologous protein to human BPI (huBPI) derived from the scorpionfish Sebastes schlegelii (scoBPI) completely escaped recognition by these autoantibodies. Moreover, scoBPI exhibited high anti-inflammatory potency towards Pa LPS and was bactericidal against MDR Pa derived from PwCF at nanomolar concentrations. In conclusion, our results highlight the potential of highly active orthologous proteins of huBPI in treatment of MDR Pa infections, especially in the presence of BPI-ANCA.
Gesehen am 18.08.2023